2004
DOI: 10.1375/twin.7.5.387
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Rates of Multiple Maternities

Abstract: We analyze the association between the rates of multiple maternities. Correlation analysis is suitable if there are at least monotonic relationships between the variables. A decreasing tendency can be observed in the rates of multiple maternities in Sweden and in its 25 counties for the period 1751–1960 and the effect of external variables can be assumed to be monotonic. After 1960, the rates of multiple maternities show marked increases, mainly caused by ovulation stimulants and the introduction of other arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Jenkins (1927Jenkins ( , 1929, Jenkins and Gwin (1940), Bulmer (1970), and later Fellman and Eriksson (2004) have tried to modify the law in order to improve it. Fellman and Eriksson (1993) have given a mathematical proof that Hellin's law cannot hold as a general rule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jenkins (1927Jenkins ( , 1929, Jenkins and Gwin (1940), Bulmer (1970), and later Fellman and Eriksson (2004) have tried to modify the law in order to improve it. Fellman and Eriksson (1993) have given a mathematical proof that Hellin's law cannot hold as a general rule.…”
mentioning
confidence: 99%
“…One application of Hellin's law is to compare the twinning rate (TWR) and the square root of the triplet rate (TRR), the cubic root of the quadruplet rate (QUR) and so on (Eriksson & Fellman, 2007;. Fellman and Eriksson (2004) considered the correlation between the TWR and the square root of the TRR in Sweden. After elimination of temporal factors, they found that the correlation was positive, but not very strong.…”
mentioning
confidence: 99%
“…Fellman and Eriksson (2004) considered the correlation between the TWR and the square root of the TRR in Sweden. After elimination of influential temporal factors, they found that the correlation was positive, but not very strong.…”
mentioning
confidence: 99%
“…Fellman and Eriksson (2004) stressed that in population studies the Hellin-transformed triplet rate can be compared with the twinning rate. We now evaluate how this holds in sibship studies.…”
Section: Twin Research and Human Geneticsmentioning
confidence: 99%